Schistosomus reflexus in dogs: Case report (2019)
The Schistosomus reflexus (SR) etymologically refers to an abdominal and / or thoracic cleft with eventration of viscera. This pathology is diagnosed more frequently in ruminants such as cattle and sheep compared to few cases reported in dogs. According to reports, this is the fourth case of SR that is reported in canines. This condition is likely caused by various factors such as endocrine, alimentary, metabolic, hereditary and teratogenic in the first third of gestation, leading to disorders in embryonic development. In this report, a two-year-old canine Pinscher that presented clinical signs of birth was taken to the Veterinary hospital. Four puppies were born; three of them presented morphological malformations, being compatible with SR. It was observed abdominal cleft associated to abdominal and thoracic ventral midline defect, eventration with exposure of viscera (liver, intestines, and spleen), cleft palate, proptosis and microcephaly .